Keratocystic Odontogenic Tumor: Case Reports and Review of Literature - Mukta B Motwani; Sunil S Mishra; Ruchi M Anand; Shirish S Degwekar; Rahul R Bhowate (Wolters Kluwer Medknow Publications, 2011)
The lesion traditionally known as odontogenic keratocyst has been renamed by WHO in 2005, as "keratocystic" odontogenic tumor as it is more appropriate and reflects its potential for local, destructive behavior. It is a benign intraosseous neoplasm of jaw, which is unusual due to its characteristic histopathological and clinical features, including potentially aggressive behavior, high recurrence rate and association with the nevoid basal cell carcinoma syndrome. The purpose of this review is to highlight the importance of proper diagnosis of keratocystic odontogenic tumor in order to prevent the recurrence due to improper surgical excision of the lesion.